The Role of Shariah Insurance and Financial Institutions in Developing Islamic Economic Law in Indonesia - Idwal Idwal; Sirman Dahwal (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: An important part of the economic law is the regulation about financial institutions insurance. In the field of insurance business development, there is a new field that is Shari'ah insurance. Novelty of shariah insurance business is the operation of its business activities based on the principles of Shari'ah derived from the Qur'an and the Hadith and the Fatwa Ulama mainly gathered in the Indonesian Council of Ulema (MUI). Because since the beginning the shari'ah insurance business is defined as a form of insurance that is based on the values contained in the teachings of Islam. Methods: This research is a doctrinal law or normative legal research, because this research is conducted with the approach of regulation and conceptual. This study is sourced from primary, secondary, and tertiary legal materials, and non-legal materials that support the subject matter. This research was conducted through the study of literature or documents. Results: The results of the study is that which distinguishes principle of insurance syar'iah with conventional insurance is Shari'ah insurance eliminates the element of uncertainty (gharar), the element of speculation or gambling (maisir), and the element of money interest (riba) in its business activities so that the participants of insurance (Insured person) feel free from tyranny practices that bring harm. Conclusion: At this time, the development of economic activity which is based on Shari'ah can be said to thrive. This is because the majority of Indonesia's population is Muslim. In addition, each Shari'ah-based economic activity prioritize in fair sharing of benefits thus in shari'ah-based economic activities do not cause any harm to the doer of this economic activity.